SCHOOL FOOD IN THE DISCOURSE OF FOOD HANDLERS IN BRAZILIAN PUBLIC SCHOOLS (REMUNOM, 2025)
This study aims to present narratives given by food handlers about school meals in Brazilian municipalities. This is a qualitative study. Fifty-seven food handlers (lunch ladies) from public schools in the capitals and municipalities in the interior of the five geographic regions of Brazil took part in the research. To collect the statements, individual interviews were used, with the help of a semi-structured questionnaire. In each school participating in the research, a lunch lady was randomly selected to be interviewed. For the analyses, the Collective Subject Discourse technique was used. The main aspects expressed in the speeches revealed that, for the lunch ladies, school meals are “a complement to home meals”, “contribute to the student's performance and learning”; It is also perceived as “a student’s right”, and “a form of education and encouragement for adequate and healthy eating”. The study concluded that for food handlers, the food served at school goes beyond the nutritional and biological dimension. Such understandings contribute to the recognition of these professionals beyond their technical multitasking, as they perceive school feeding as an element of enforcing and maintaining rights, and as a fundamental practice for education and learning.